BIMBINGAN KELOMPOK DENGAN TEKNIK SELF-MANAGEMENT UNTUK MENGEMBANGKAN KEMANDIRIAN SISWA: Studi Eksperimen terhadap Kemandirian Siswa Kelas X SMA Negeri 8 Tasikmalaya Tahun Ajaran 2022/2023 - Megafitri, - (2023)
Megafitri, 1803519. Group Mentoring with Self-management Techniques to Develop Student Autonomy (Experimental Study on the Autonomy of 10th Grade Students of SMA Negeri 8 Tasikmalaya Academic Year 2022-2023) Guided by Dr. Anne Hafina Adiwinata, M. Pd., and Dr. Amin Budiamin, M. Pd. Adolescence is a developmental phase that has an important role in one's life. Autonomy is one of the important developmental traits that must be gained in the adolescent phase. Autonomy is the capacity to self-govern and express one's own action, which is not dependent on others, either emotionally, behaviorally, or cognitively. This research aims to determine the profile of autonomy, program formulation, and effectiveness of group mentoring with self-management techniques to develop the autonomy of 10th grade students at SMAN 8 Tasikmalaya. The research implemented a quantitative approach with a quasi-experimental non-equivalent pre-test and post-test control group design. The inventory implemented for this research was an autonomy instrument of 50 items. This research involved 336 students of 10th grade students of SMAN 8 Tasikmalaya applying the convenience sampling technique. The results indicated that group mentoring with self-management techniques was effective in developing the autonomy of 10th grade students. Recommendations are addressed for mentoring and counseling teachers to implement group mentoring with self-management techniques with some modifications to match the needs and characteristics of students. Keywords: Adolescence; Autonomy; Group Mentoring; Self-management